Pengaruh Sifat Machiavellian Dan Power Distance Terhadap Keputusan Whistleblowing - Hesti Eka Pratiwi; Sany Dwita (Universitas Negeri Padang, 2020)
A number of factors affects the auditors to report unethical behavior in their organizaton. Given the importance of the Machiavellian construct on informing a wide range of ethics research, we focus on gaining a better understanding of Machiavellian within the whistleblower context. We examine the effect of Maciavellian on whisleblowing, focusing on the underlying mechanism through which Machiavelian affects the decision of whistleblowing. Further, because higher Machiavellian are expected to be less likely to report wrongdoing, we examine the ability of an low power distance to increase whistleblowing decision. As Hoftsede research of Indonesian culture, Indonesia has high score (78) on power distance dimention. This research uses experimental method to 67 students of Undergraduate of Accounting in UNP. By using two-case scenarios, partispants were asked to answer the possibility to whistleblow the unethical behavior that occurred in the organization which was done by their manager or peer. The results of this research indicate that the auditors with high Machiavellian has no negative impact for whistleblowing decision. We also find that low power distance has positif impact for whistleblowing decision. Taken together, these findings contribute to the exising literature on accounting ethics.